2018
DOI: 10.1088/1361-6528/aab6a3
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of resistive switching properties in Al2O3bilayer-based atomic switches: multilevel resistive switching

Abstract: Atomic switches are considered to be building blocks for future non-volatile data storage and internet of things. However, obtaining device structures capable of ultrahigh density data storage, high endurance, and long data retention, and more importantly, understanding the switching mechanisms are still a challenge for atomic switches. Here, we achieved improved resistive switching performance in a bilayer structure containing aluminum oxide, with an oxygen-deficient oxide as the top switching layer and stoic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 39 publications
0
44
0
Order By: Relevance
“…We will discuss more about the self-compliance effect on the synaptic behavior in the pulse switching mode. The homogeneous switching (type 3) can be obtained by using a negative differential resistance effect before the electroforming or set processes ( Figure S1 ) [ 34 , 46 ]. The initial reset process in a negative bias occurs probably because of the abundant initial traps in the Al 2 O 3 layer.…”
Section: Resultsmentioning
confidence: 99%
“…We will discuss more about the self-compliance effect on the synaptic behavior in the pulse switching mode. The homogeneous switching (type 3) can be obtained by using a negative differential resistance effect before the electroforming or set processes ( Figure S1 ) [ 34 , 46 ]. The initial reset process in a negative bias occurs probably because of the abundant initial traps in the Al 2 O 3 layer.…”
Section: Resultsmentioning
confidence: 99%
“…As conductive filaments dictate both the location and mechanism of transport, and ultimately enables information storage and multi-functionality, obtaining spatially-resolved information involving their construction is required to maximize the enhancements in performance. Three-dimensional conductive-AFM (3D c-AFM) tomography, [51][52][53][54] a recently developed AFM approach, combines the sensitive force control in the zdimension of the AFM with a hard, conductive diamond probe attached to a high stiffness cantilever (~ 50 N/m) to sequentially remove material layer-by-layer and subsequently measure the local current, thus yielding a slice-and-view approach to observe conductive filaments within oxide-based memristors.…”
Section: Distinguishing Filament Morphology Via 3d C-afm Nanotomographymentioning
confidence: 99%
“…A clear trend in the ±V STOP voltagedependent I SET , I RESET , V SET , and V RESET was observed from the experimental data. These results indicated that the size of the conductive filament was modulated as a function of CC 47 . The nature of RS properties can be elucidated by the value of η (I SET /I CC ) or (I RESET /I CC ).…”
Section: Resultsmentioning
confidence: 77%